Moderating Effect of Earnings Management in the Relationship between Sustainability Reporting Initiatives and Value Relevance - Mashiur Rahman; Siti Zaleha Abdul Rasid; Rohaida Basiruddin (Universitas Pasundan, 2020)
The purpose of this study is to investigate whether sustainability disclosures are associated with value relevance in Bangladesh. The moderating effect of earnings management (EM) is also examined to observe the right direction in this relationship. Based on prior studies on sustainability disclosure and global reporting initiatives guidelines, this research uses the content analysis approach to assess the magnitude of sustainability initiatives of 30 Bangladeshi banking companies over the period 2009–2017. The Ohlson price model and discretionary accruals are also employed as measures of value relevant of sustainability disclosure and EM, respectively. The findings state that sustainability reports positively affect the equity value, whereas EM negatively moderates the direction of this association. The results also confirm that management should be responsive of the impending capital market effects of voluntary disclosures regarding sustainability issues. These findings could have several implications for banks, investors, and policymakers.